The emerging sociocultural issues during Kelantan River Basin flood disaster: an Ngos perspective - Othman, Mohhidin; Ismail, Sumarni (American - Eurasian Network for Scientific Information, AENSI Publications, 2016)
This paper explores the various issues emerged during the Kelantan river basin flood disaster using a qualitative research approach. The methodological approach was based on a focus group discussion held with non-governmental organization (NGOs) representatives who relate their experiences during the flood at Kelantan River basin in 2014. The interviews were transcribed verbatim and content analyzed and the primary findings identified some sociocultural aspects from their flood disaster management experiences. The issues emerged from the qualitative data that specifically related by the informants based on their experiences in terms of preparedness, planning and deployment of personnel and resources. The study ha d identified a total of 50 issues related to the disaster which were later the med into 5 dimensions. The dimensions were categorized into victims’ attitude, their religious background, the existing infrastructure and nature, as well as their political background and issues related to social media and communication. Some of the sociocultural issues highlighted could assist in the identification of best practices and could also be a good lesson learned exercise for future mitigation of a similar disaster in Malaysia.